Tengdan Capsule Prevents Hypertensive Kidney Damage in SHR by Inhibiting Periostin-Mediated Renal Fibrosis - Xiaoli Du; Xiaoli Du; Xiaoli Du; Qianqian Tao; Qianqian Tao; Hongxia Du; Hongxia Du; Zhenbang Zhao; Yu Dong; Yu Dong; Shuang He; Shuang He; et al. (Frontiers Media S.A., 2021)
BACKGROUND: Hypertension-induced renal damage is a serious and complex condition that has not been effectively treated by conventional blood pressure-lowering drugs. Tengdan capsule (TDC) is a China FDA-approved compound herbal medicine for treating hypertension; however, its chemical basis and pharmacological efficacy have not been fully investigated in a preclinical setting.METHODS: High-performance liquid chromatography (HPLC) was used to identify and quantify the major chemical components of TDC extracted from ultrapure water. Adult spontaneously hypertensive rats (SHR) and age/sex-matched Wistar Kyoto normotensive rats (WKY) were both treated with TDC, losartan, or saline for one month, and their blood pressure (BP) was monitored at the same time by tail-cuff BP system. Biochemical indexes such as urine creatinine (CRE) and blood urea nitrogen (BUN) were determined. Kidney tissue sections were examined with (H&E), and Masson staining to evaluate the pathological effect of TDC on SHR's kidneys. After TDC treatment, the differentially expressed proteins in the kidneys of SHR were identified by the TMT-based quantitative proteomics analysis, which may provide the targets and possible mechanisms of TDC action. In addition, Western blot analysis, RT-qPCR, and ELISA assays were carried out to further verify the proteomics findings. Finally, two different models involving in vitro renal injuries were established using human kidney HEK293 cells; and the molecular mechanism of TDC kidney protection was demonstrated.RESULTS: Seven chemical compounds, namely Notoginsenoside R1, Ginsenoside RG1, Ginsenoside Re, Ginsenoside Rb1, Sodium Danshensu, Protocatechualdehyde, and Salvianolic acid B, were identified and quantified from the water-soluble extracts of TDC by HPLC. In vivo study using rats showed that TDC effectively reduced BP, BUN, and CRE levels and attenuated renal fibrosis in SHR, and ameliorated damage to the kidneys. Proteomics and subsequent bioinformatics analyses indicated that periostin-mediated inflammatory response and TGFβ/Smad signaling pathway proteins were closely related to the therapeutic effect of TDC in rat kidneys. Western blot analysis and RT-qPCR showed that TDC markedly downregulated the mRNA and protein expression of periostin in renal tissues compared to the untreated SHR. In addition, TGF-β and COL1A1 mRNA levels also decreased in SHR renal tissues following TDC treatment. In vitro studies showed that low to medium doses of TDC down-regulated the expression of periostin in the injury model of HEK293 cell. In addition, medium to high doses of TDC significantly inhibited collagen deposition in TGFβ1-induced HEK293 cell fibrosis.CONCLUSIONS: Major components from the compound herbal medicine Tengdan Capsule are identified and quantified. TDC effectively lowers blood pressure and protects against renal damage caused by hypertension in SHR. Mechanistically, TDC blocks periostin by regulating the TGF-β/Smad signaling pathway in the kidney, both in vivo and in vitro. Preventing periostin-mediated renal fibrosis and inflammation might be a promising strategy for treating a hypertensive renal injury.